ANALISIS KESALAHAN BAHASA PADA PERCAKAPAN BAHASA ARAB MAHASISWA PROGRAM STUDI PENDIDIKAN BAHASA ARAB (PBA) STAIN JURAI SIWO METRO TAHUN AKADEMIK 2013/2014 - Walfajri, Walfajri (JURNAL TAPIS, 2014)
This study is aimed at classifying the kinds of errors in Arabic conversations of students majoring in Arabic at the State Islamic College of Jurai Siwo Metro in Academic Year 2013/2014, describing the frequency of the language errors, and explaining the factors that caused the language error. The data were collected through observation, field notes, and tape recording. The results showed that errors in Arabic conversations of the students can be classified in three kinds of languages errors, namely: (1) the pronunciation errors, (2) the morphology errors, and (3) the syntax errors. On the kind of pronunciation errors, the highest frequency of errors occurred at pronunciation of / Ø¶/, / Ø«/, / Ø¹/, and / Ã/. On the kind of morphology errors, the highest frequency of errors occurred at tashrif fiâil madhiy and tashrif fiâil mudhariâº. On the kind of syntax errors, the highest frequency of errors occurred at the structure of mudhaf-mudhaf ilaih, naâºat-manâut, and jarmajrur. The factors that caused the pronunciation errors can be categorized as the inter-language errors. While the factors that caused morphology errors and syntax errors can be categorized as the intra-lingual errors.Keywords:Language errors, inter-language errors, intra-language errors